From kinship networks to culture of relatedness: a shift of safety nets during health pandemics in the kenyan context - Nyabundi, Agnetta Adiedo (Frontiers in Public Health, 2023)
Evidence suggests that, during pandemics such as COVID-19, people with low incomes within developing countries suffered disproportionately. Households across countries differentially experienced the socio-economic impact of the pandemic. In sub-Saharan Africa, the extended family and the community have provided valuable support in crises, given that state-administered backing may not be sufficient or may differ from the family's expectations. Many studies have been conducted on community safety nets, yet little description and understanding of community safety nets has been provided. The components of the non-formal safety nets are yet to be adequately defined or evaluated for effectiveness. Traditional family and community safety nets have been under stress due to the impact of COVID-19. Many countries, including Kenya, have associated COVID-19 with an increased number of households facing social and economic crises. Families and communities got fatigued due to the extended period and the further strain the pandemic had on individuals and societies. Utilizing existing literature on the socio-economic impact of COVID-19 in Kenya and the roles and perceptions of community safety nets, this paper seeks to explain the roles and perceptions of social relationships and kinship networks as safety nets in Africa, specifically in the Kenyan context. This paper employs the concept of culture of relatedness to understand the informal safety nets in Kenya better. During the COVID-19 pandemic, individuals strengthened the previously weakened kinship structures. They addressed some of the challenges experienced within the networks through the involvement of neighbors and friends embracing the culture of relatedness. Therefore, government strategies for social support during pandemics need to design programs to strengthen the community safety nets that remained resilient throughout the health crisis.